Simulation study of flow in Fluidized Bed Reactor: vortex distribution / Zaidi M.R. and Mahadzir M.M. - M.R., Zaidi; M.M., Mahadzir (2014)
The developments in research of the simulation study of flow in fluidized bed are briefly introduced. The problem related to the fluidized bed reactors is also reported. The characteristics of the fluidization were discussed further in detail. The distributor designs and their impacts to the flow in the fluidized bed were also studied. The distributor was designed and used in the simulation of flow of fluidized bed by using SolidWorks. The flow simulation was conducted through a series of procedure; initializing the mesh, calculating control option, inserting boundary condition, choose goals, and running the analysis. The parameter used was volumetric flow rate, using 0.00000007 m3/s, 0.00001 m3/s, 0.0001 m3/s, 0.001 m3/s, and 0.0005 m3/s. The results of each flow was obtained; the 1st run had non-existent flow, 2nd run had transition flow with minimum vortex, 3rd run had developed flow but dead zones still persists, 4th run had perfect flow but impractical, and 5th run had perfect flow with minimum dead zones. It was concluded that the flow in the 5th run is the best out of them.